PELANGGARAN ETIKA PROFESI BANKIR DALAM DIMENSI KEJAHATAN PERBANKAN - Ida Nurhayati; Rita Farida (Politeknik Negeri Jakarta, 2018)
Abstract This research is part of my dissertation that discusses ethical violations including banking crimes, which are subtle (criminogenic). This study aims to explain that ethics can be used as a guideline in running banking activities in addition to the legal regulations that accompany banking activities. This research uses a qualitative approach using a model put forward by Graaf-Huberts (2008) that is